HackNotes Network Security Portable Reference - Horton, Michael (McGraw-Hill, 2011)
Here’s the quickest means to network security. Information systems security consultant Mike Horton provides trustworthy tips to help IT professionals deliver ready-made hacking and security architecture solutions. Plus, learn to use a full complement of effective, up-to-date security tools.